ANALYSIS DETERMINATS OF EARNINGS MANAGEMENT MANUFACTURING COMPANIES LISTED ON THE IDX - Bulutoding, Lince; Suwandi, Memen; Anwar, Puspita Hardianti; Sari, Nur Rahmah; Kadir, Nur An’nizar (Jurnal Iqtisaduna, 2019)
This study aims to examine the variables that are determinants of earnings management in manufacturing companies both direct effect and indirect effect on the IDX. The type of this study is a quantitative. The population of the study is manufacturing companies listed on the IDX in 2015-2017. The study used data obtained from Purposive sampling method of the company’s financial statements accessed through www.idx.com (N=81). Data analysed by Structural Equation Modeling (SEM) using AMOS program. The study found that firm size directly had no significant effect on tax avoidance, sales growth directly had a significant effect on tax avoidance, tax avoidance directly had a significant effect on earnings management. Firm size directly had no effect on earnings management, sales growth directly had a significant effect on earnings management. Firm size does not affect earnings management through tax avoidance. While Sales growth has a significant effect on earnings management through tax avoidance. The implications of this study are: provide input for company practitioners to be more careful in conducting earnings management because they should not be considered as an effort to Tax avoidance by the relevant agencies. This study can help investors in analyzing financial statements in order to understand the practice of earnings management conducted by companies with the aim of tax avoidance that will have a long impact on the continuity of the company. This study provides information for agencies involved in determining policies in the capital market.